Uniqueness of Meromorphic Functions and Differential Polynomials - Jin-Dong Li (International Journal of Mathematics and Mathematical Sciences)
We study the uniqueness of meromorphic functions and differential polynomials sharing one value with weight and prove two main theorems which generalize and improve some results earlier given by M. L. Fang, S. S. Bhoosnurmath and R. S. Dyavanal, and so forth.